Evaluasi Program Literasi Perspektif Model CIPP Pada Sman Tiang Pumpung Kepungut - Sumira, Tati; Putri Kartiwi, Asti (Manajer Pendididikan, 2024)
This research aims to describe the results of the literacy program evaluation using the CIPP model at SMAN Tiang Pumpung Kepungut. The research method used in this research is an evaluation study using the CIPP model (context, input, process and product) with qualitative descriptive techniques. The research results stated that the context of the literacy program in the form of a basic understanding of implementation was good because it already had a basis, objectives and cooperation built by the school. The literacy program input consisting of material and human resources has also been implemented well, the literacy program process is running well, where the program implementation is in accordance with planning, and the product in the form of students' communication skills is very good. Suggestions were conveyed to teachers and school principals to continue to be consistent in implementing this program